Prognostic impact and risk factors of low body mass index in patients undergoing liver transplantation. Issue 9 (27th July 2017) - Lee, Jin‐Chiao; Doush, Wael M. A.; Wang, Yu‐Chao; Cheng, Chih‐Hsien; Wu, Tsung‐Han; Chen, Yi‐Chan; Soong, Ruey‐Shyang; Wu, Ting‐Jung; Chou, Hong‐Shiue; Chan, Kun‐Ming; Lee, Wei‐Chen; Lee, Chen‐Fang
Abstract: We aimed to investigate the effect of body mass index (BMI) on the overall survival rates and to identify the risk factors associated with adverse outcomes. A total of 381 adult‐to‐adult living donor liver transplantations performed were retrospectively analyzed. These patients were classified according to the BMI categories established by the World Health Organization: The underweight group (BMI<18.5 kg/m 2 ) and the non‐underweight group (BMI≥18.5 kg/m 2 ). The underweight group had significantly worse outcomes, compared with that of the non‐underweight group (5‐year overall survival: 45.6% vs 74.6%, P <.001). Underweight patients with CD4/CD8 ratio <1.4 had a significant worse prognosis, compared with those with CD4/CD8 ratio ≥1.4. (The 1‐, 3‐, and 5‐year overall patient survival rates in both groups were 71.0% vs 20%, 58.9% vs 0%, and 53.6% vs 0%, respectively, P =.002.) In the multivariate analysis, only CD4/CD8 ratio <1.4 was an independent poor prognostic factor (hazard ratio=7.063, 95% confidence interval=1.329‐37.547, P =.022). Conclusions: Pre‐operative CD4/CD8 ratio <1.4 is an independent poor prognostic indicator for underweight patients undergoing liver transplantation. Early intervention in replenishing the nutrient deficit and cautious use of immunosuppressive regimens are essential to prepare this high‐risk population for a more successful liver transplantation.